2017
DOI: 10.1007/s10549-017-4132-9
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs miR-7 and miR-340 predict response to neoadjuvant chemotherapy in breast cancer

Abstract: Purpose miRNAs have been linked to chemosensitivity of breast cancer cells in-vitro. In patients, however, there is no clinically validated method for predicting chemotherapy response. The aim of this study was to assess whether I) a specific pattern of miRNA expression in pretherapeutic biopsies can predict response to neoadjuvant chemotherapy, and II) differential miRNA expression in residual tumor after completion of chemotherapy allows further prognostic stratification of non-responding patients. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 52 publications
3
33
0
Order By: Relevance
“…Regarding miR-340-5p, the patients with recurrence had higher levels of miR-340 at their primary site as well as in the serum. Several studies have suggested the role of miR-340 as tumor suppressor gene [ 45 , 46 ], but one report demonstrated the association between miR-340 and chemoresistance [ 47 ]. Raychaudhuri et al reported that the patients with high expression of miR-340 in pretherapeutic biopsies in breast cancer were less likely to achieve pathological complete response (pCR).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding miR-340-5p, the patients with recurrence had higher levels of miR-340 at their primary site as well as in the serum. Several studies have suggested the role of miR-340 as tumor suppressor gene [ 45 , 46 ], but one report demonstrated the association between miR-340 and chemoresistance [ 47 ]. Raychaudhuri et al reported that the patients with high expression of miR-340 in pretherapeutic biopsies in breast cancer were less likely to achieve pathological complete response (pCR).…”
Section: Discussionmentioning
confidence: 99%
“…Raychaudhuri et al reported that the patients with high expression of miR-340 in pretherapeutic biopsies in breast cancer were less likely to achieve pathological complete response (pCR). MiR-340 is predicted to regulate several genes which are associated with tumor growth and proliferation including Jun- and Fos oncogene, and Cyclin Dependent Kinase 5 [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The miR‐7‐5p upregulation reportedly inhibits cell proliferation and induces apoptosis of BC cells and tissues in vitro and in vivo (Y. Shi et al, ). Also, studies have shown that miR‐7‐5p directly targets Raf1 gene during lapatinib‐induced metastasis by IL‐6 expression in triple‐negative BC, and its reduced expression plays a key role in resistance of BC to neoadjuvant chemotherapy (Hsiao et al, ; Raychaudhuri et al, ). Notably, Raf1 gene has a crucial function in activating PI3K/Akt signaling pathway which has been shown to be complicated in the drug resistance of BC cells (Yuan Miao et al, ).…”
Section: Cerna Interplay In Bc Development and Pathogenesismentioning
confidence: 99%
“…Differentially expressed miRNAs have been shown to be associated with different molecular subtypes of breast cancer (13). Several miRNAs, whose expression is associated with the clinical outcomes of breast cancer, serve as oncogenes or tumor suppressors in breast cancer (14)(15)(16). Recently, miR-532-5p was demonstrated to be significantly upregulated in TNBC tissues compared with normal breast tissues (17).…”
Section: Introductionmentioning
confidence: 99%